2004
DOI: 10.1113/jphysiol.2004.063859
|View full text |Cite
|
Sign up to set email alerts
|

The human tumour suppressor gene SLC5A8 expresses a Na+–monocarboxylate cotransporter

Abstract: The orphan cotransport protein expressed by the SLC5A8 gene has been shown to play a role in controlling the growth of colon cancers, and the silencing of this gene is a common and early event in human colon neoplasia. We expressed this protein in Xenopus laevis oocytes and have found that it transports small monocarboxylic acids. The electrogenic activity of the cotransporter, which we have named SMCT (sodium monocarboxylate transporter), was dependent on external Na + and was compatible with a 3 : 1 stoichio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
139
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(155 citation statements)
references
References 44 publications
12
139
1
1
Order By: Relevance
“…For immunohistochemistry, deeply anesthetized animals were perfused via the aorta with physiological saline, followed by 4% paraformaldehyde in 0.1 M phosphate buffer (PB) (pH 7.4). The tissues menacid (the 1-carbon SCFA) and acetic acid (the 2-carbon SCFA) than upon that of larger SCFAs (6). In that study, L-lactate and pyruvate also induced large currents through Slc5a8 (6).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…For immunohistochemistry, deeply anesthetized animals were perfused via the aorta with physiological saline, followed by 4% paraformaldehyde in 0.1 M phosphate buffer (PB) (pH 7.4). The tissues menacid (the 1-carbon SCFA) and acetic acid (the 2-carbon SCFA) than upon that of larger SCFAs (6). In that study, L-lactate and pyruvate also induced large currents through Slc5a8 (6).…”
mentioning
confidence: 76%
“…The tissues menacid (the 1-carbon SCFA) and acetic acid (the 2-carbon SCFA) than upon that of larger SCFAs (6). In that study, L-lactate and pyruvate also induced large currents through Slc5a8 (6). Early studies have demonstrated the existence of a Na + -coupled lactate transport system in the brush border membrane of the kidney (2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a potent membrane transporter for SCFA, namely solute-linked carrier 5a8 (slc5a8), was identifi ed as a Na + -coupled co-transporter for SCFA and lactate (5,12,20). In contrast to MCT, which functions as H + -coupled electroneutral transporters, slc5a8 functions as a Na + -coupled electrogenic transporter.…”
Section: Methodsmentioning
confidence: 99%
“…Short‐chain fatty acids produced in the colon are then taken up into the circulation by monocarboxylate transporters (Coady et al . 2004) and by free diffusion. Thus, although changes in host metabolism or in dietary intake may additionally modulate serum SCFA concentrations, it is clear that gut microbial production is a major determinant of circulating SCFAs.…”
Section: Introductionmentioning
confidence: 98%